PENGARUH INFLASI, KURS, SUKU BUNGA SBI, DOW JONES, DAN NIKKEI 225 TERHADAP INDEKS HARGA SAHAM GABUNGAN PADA BURSA EFEK INDONESIA PERIODE 2012-2016 - IMAN ZABIDI, IQBAL; ASANDIMITRA HARYONO, NADIA (Jurnal Ilmu Manajemen (JIM), 2018)
The purpose of the study is to determine the effect of inflation, exchange rate, SBI rate, DJIA, and NIKKEI 225 against Composite Stock Price Index for 2012-2016 Period. The dependent variable in this study is JCI, while the independent variables include inflation, exchange rate, SBI rate, Dow Jones, and NIKKEI 225. 60 saturated sampling are used as sample determinant based on monthly schedule period January 2012 - December 2016. This research use multiple linear regression analysis method. The study outcomes indicate that inflation, exchange rate, and SBI rates do not have a negative effect on JCI. NIKKEI 225 has no positive effect on JCI. While Dow Jones has a significant positive effect on the movement of IHSG. The Adjusted R square value are 0.244 which means that the movement of IHSG influenced 24.4% by the variables on this study and 75.6% is explained by variables outside this study. Keywords: Inflation, Exchange Rate, SBI Rate, DJIA, NIKKEI 225, IHSG